Parmenides and To eon : reconsidering muthos and logos - Wilkinson, Lisa Atwood (Continuum studies in ancient philosophy., 2009)
This is an important new study offering a new historical and philosophical insight Parmenides in light of the oral tradition of ancient Greece. "Parmenides and To Eon" offers a new historical and philosophical reading of Parmenides of Elea by exploring the significance and dynamics of the oral tradition of ancient Greece. The book disentangles our theories of language from what evidence suggests is an archaic Greek experience of speech. With this in mind, the author reconsiders Parmenides' poem, arguing that the way we divide up his text is inconsistent with the oral tradition Parmen.